Assessment of genetic diversity by phenological traits, field performance, and Start Codon Targeted (SCoT) polymorphism marker of seventeen soybean genotypes (Glycine max L.) - Abdel-Sattar, Mahmoud; Zayed, Ehab M.; Abou-Shlell, Mohamed K.; Rihan, Hail Z.; Helal, Ahmed A.; Mekhaile, Nabil E.G.; El-Badan, Ghada E. (PeerJ, 2024)
The Egyptian-farmed soybeans have a wide range of genetic diversity which is most important in plant improvement programs in order to develop new higher yielding soybean genotypes. The present study is designed to determine the genetic variability among seventeen genotypes of cultivated soybean (Glycine max L.) by examining the phenotypic level at the seedling stage, field performance over two years 2022/2023 and genetically using Start Codon Targeted (SCoT) markers. Results indicated that the SCoT markers, 100 seed weight, and tip angle (TA) traits were positively correlated with H2L12, DR 101, H15L5, and H117 genotypes. In addition, the number of branches per plant and plant height were associated with H113, H32, Crowford, H129, and D7512035. Furthermore, the length of the first internode (LFI), root width (RW), root length (RL), and shoot length (SL) were more associated with Giza 111, NC105, and Hutcheson. The hierarchical cluster analysis (HCA) and its associated heatmap explored the differences among the genotypes. It showed that all examined parameters were clustered into four distinct clusters. The obtained results showed that genotypes NC105, H30, D75_12035, and H2L12 have promising phenological and morphological traits besides tracking the inheritance of nearby genes surrounding the ATG translation start codon since they are in a monoclades. The obtained results will help the breeder plan appropriate selection strategies for improving seed yield in soybeans through hybridization from divergent clusters.
Keywords: Field performance; Genetic diversity; Phenological; Soybean; Start codon targeted; Yield